Velocity combining lean, six sigma, and the theory of constraints to achieve breakthrough performance : a business novel - Jacob, Dee (Free Press, 2010)
"Velocity" presents a business improvement method that combines Six SIGMA, Lean Thinking, and the Theory of Constraints.